A Method of Digital Computation for SCR Circuits - Kutman, Tamer (Institute of Electrical and Electronics Engineers (IEEE), 1974)
It is shown in this paper that it is possible to derive generalized equations for computation of electrical circuits containing SCR elements. Any classical method of circuit analysis can be used applying the nonlinear mathematical model given for the SCR. In order to get this model, a binary logic state variable is doped to the equation which is obtained by a Boolean function. The derivation of this mathematical model and the application of the method to an impulse-commutated inverter with an RL load are presented.